Analysis of Students’ Report Writing from SFL-GP Perspective and Its Relation to Students’ Proficiency - Monalisa Pasaribu; Tiurma Lumban Lumban; Hernawati Samosir (Jurnal Teknologi Informasi dan Pendidikan, 2021)
Academic writing is one of important skill to have students in tertiary education, including students of Information Technology Diploma. Using Systemic Functional Linguistics Genre Pedagogy (SFL GP), the students report writings are investigated, his research aims at investigating how students comprehend SFL GP in their report writing and find out the relationship between students’ knowledge of SFL GP with their language proficiency. The texts are analyzed using the genre division by Rose and Martin. The results of the analysis will be used to investigate if the knowledge of genre writing for technology-based students is related to their language proficiency. This research contributes to better use of genre pedagogy for science students, more specifically, students of Information Technology.